ChemInform Abstract: Copper‐Catalyzed Cycloaddition Between Hydrogen Phosphonates and Activated Alkenes: Synthesis of Phosphonoisoquinolinediones. Issue 20 (April 2016) - Wu, Ju; Gao, Yuzhen; Zhao, Xin; Zhang, Liangliang; Chen, Weizhu; Tang, Guo; Zhao, Yufen
Abstract: The phosphonation‐cyclization sequence of various methacroylbenzamides with phosphonates provides a rapid access to the title products in moderate to high yields.